Now We Are Six - A. A. Milne (U.S.A Puffin Books; Reissue edition, 1992)
More entertaining verses and delightful pictures in the style of When We Were Very Young. "Gay verses about all manner of things, which with their original rhythm dance their way into memory."--Four to Fourteen, 1927
Keywords: Poetry